Ankle angle variability during running in athletes with chronic ankle instability and copers - Wanner, Philipp; Schmautz, Thomas; Kluge, Felix; Eskofier, Björn; Pfeifer, Klaus; Steib, Simon (Gait & posture, 2019)
Background: Individuals with chronic ankle instability (CAI) demonstrate altered ankle kinematics during running compared to uninjured individuals; however, little is known about differences between individuals with CAI and those who recover successfully from an index sprain (copers). Methods: Thirty-two young male athletes with prior ankle sprain were investigated, eighteen with CAI and fourteen copers. Instrumented running analysis was performed on a treadmill at two velocities: moderate (2.63 ± 0.20 m/s, rate of perceived of exertion = 14/20); and high velocity (3.83 ± 0.20 m/s). Mean ankle kinematics and stride-to-stride variability were analyzed applying the statistical parametric mapping method. Results: At both running velocities, no statistically significant differences in mean ankle kinematics were observed. At high running velocity, athletes with CAI demonstrated significantly increased frontal plane variability at 17-19% of the running gait cycle (p = 0.009). Additionally, large between-group effect sizes (Hedges’ g ≥ 0.8) may potentially indicate increased frontal plane variability during initial contact and terminal swing, as well as decreased variability in sagittal plane at 34-35% in CAI. A similar tendency existed at moderate velocity, with large effect sizes indicating decreased dorsiflexion at 75-89% in CAI, as well as an increased frontal plane variability at 16-25%, and 97-99%. Discussion: Compared to copers, individuals with CAI demonstrate increased variability of ankle kinematics - mainly in the frontal plane and particularly during stance phase - while mean ankle kinematics seems minimally affected. Increased ankle variability at high running velocity may best reflect persisting sensorimotor control deficits in athletes with chronically instable ankles.